PENERAPAN MODEL PEMBELAJARAN PjBL MENGGUNAKAN MEDIA VIDEO PEMBELAJRAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - CHAMILATUR ROCHMAH; Ifa Seftia Rakhma Widiyanti (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to improve student learning outcomes through the PjBL learning model in science and science learning Chapter 5. Using the classroom action research method (PTK). The data analyzed in this research is the application of student activity data and student learning outcomes data. The student activity observation data in cycle I obtained a success percentage of 54.376%, the student activity observation data in cycle II obtained a success percentage of 73.953%, and the student observation data in cycle III obtained a success percentage of 92.083%. Data on precycle learning outcomes obtained a completion percentage of 6.7% of students who completed 1 child and 14 students who did not complete. These learning outcomes are still below the minimum completeness criteria level. To improve student learning outcomes, researchers conducted research using the application of the PjBL learning model. The learning outcomes obtained from precycle to cycle I experienced an increase in the percentage of completion of 34% with, there were 5 students who had completed and 10 students who had not completed. In cycle II there was an increase in the completion percentage of 54%, there were 8 students who had completed and 7 students who had not completed. In cycle III there was an increase in the percentage of completion of 100%, there were 15 students who completed the class IV total of 15 students. Can be concluded that the application of the PjBL learning model can improve the learning outcomes of class IV UPT SDN 2 Bajingjowo students.